The Prognostic and Risk Factors for Children With High‐Risk Mature B‐Cell Non‐Hodgkin's Lymphoma: A Retrospective Multicenter Study - Xiaoming Wang; Luping Ding; Yongjun Fang; Jie Yan; Ju Gao; Liangchun Yang; Aiguo Liu; Jun Lu; Jingfu Wang; Aijun Zhang; Yijin Gao; Xiuli Ju (Cancer Medicine)
ABSTRACT Backgrounds and Aims Our previous study (CCCG‐BNHL‐2015) reported the treatment strategies and outcomes of pediatric B‐cell non‐Hodgkin's lymphoma (B‐NHL) in China which showed that children in low‐risk groups already have a dramatically favorable prognosis. However, for high‐risk groups, the prognosis still needs to be improved. In this study, we aimed to identify the factors influencing prognosis in high‐risk groups (stage III and stage IV). Results Our results revealed that gender, lactate dehydrogenase (LDH) level, stage at the time of diagnosis, and early complete remission (CR) achievement were significant factors influencing prognosis (p < 0.05). The 3‐year EFS rate for R4 group patients without rituximab treatment was only 25.0% ± 20.4%. Among all patients in stage IV, the 5‐year EFS rates for those with involvement of only bone marrow (BM) or central nervous system (CNS) were 83.0% ± 4.5%, 81.8% ± 8.2%, but the 5‐year EFS rates for those with both BM and CNS involved were only 37.5% ± 15.3% (p = 0.002). For stage III patients with LDH ≥ 4N, the 5‐year EFS rates for those achieving CR and those not achieving CR after 2 treatment cycle were 88.9% ± 5.2% and 67.9% ± 7.3%(p = 0.036). Conclusions Therefore, R4 group patients benefited from rituximab treatment. However, children at stage III, LDH ≥ 4N not achieving CR after the 2nd treatment cycle, and those with both BM and CNS involved are still at a very high risk of treatment failure. This study serves as a crucial reference for optimizing risk stratification, refining treatment categorizations, and optimizing treatment protocols.